2012
DOI: 10.1080/17458080.2011.630151
|View full text |Cite
|
Sign up to set email alerts
|

A simple one-step anodising method for the synthesis of ordered porous anodic alumina

Abstract: Porous anodic alumina (PAA) has been produced on aluminium substrate by single-step anodising at 50 V in 0.3 M oxalic acid at 15 C for 60 min. The highly ordered pore and cell structure was achieved by subjecting the PAA to oxide dissolution treatment in a mixture of chromic and phosphoric acids. The nanostructure prior and post-oxide dissolution treatment was examined under scanning electron microscope. It was found that the oxide dissolution treatment improves the regularity of the cell and pore structure si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Providing that the pore arrangement is not an important issue for the production of free standing NWs, we chose one-step anodization with the main objective of reducing the synthesis time for the preparation of the AAO templates. In the cited works [ 35 , 36 , 37 ], sulphuric and oxalic acids were used as electrolytes at temperatures from near 0 C to 15 C to obtain AAO templates with a pore diameter in the range of 20–50 nm. In this work, we explored the use of oxalic acid at room temperature (25 C) because it is cost-effective in terms of time and investment—there is no need for cooling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing that the pore arrangement is not an important issue for the production of free standing NWs, we chose one-step anodization with the main objective of reducing the synthesis time for the preparation of the AAO templates. In the cited works [ 35 , 36 , 37 ], sulphuric and oxalic acids were used as electrolytes at temperatures from near 0 C to 15 C to obtain AAO templates with a pore diameter in the range of 20–50 nm. In this work, we explored the use of oxalic acid at room temperature (25 C) because it is cost-effective in terms of time and investment—there is no need for cooling.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, although very versatile for research and lab-prototypes, the commercial application of NWs using AAO is still limited by their fabrication process, which is expensive, due to the high costs associated with the high-purity Al (99.999%) normally used as the starting material, as well as with the low temperature and large anodization time. Single-step anodization was studied by some authors as a modification of the most well-known two-step anodization with the main objective of reducing the synthesis time of alumina templates [ 34 , 35 , 36 , 37 ]. These approximations reduce the total anodization time, producing templates with pore arrangements that are far less ordered than those obtained using two-step anodization.…”
Section: Introductionmentioning
confidence: 99%
“…After the anodizing process, the substrate was rinsed thoroughly with ethanol followed by distilled water and dried. The PAA was treated with oxide dissolution treatment to reveal the well-ordered PAA formed beneath the initially formed disordered PAA [14]. The surface morphology of the alumina layer was investigated using the field emission scanning electron microscope (FESEM) and energy-dispersive X-ray spectroscopy (EDX).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, metal oxide nanostructures can be prepared directly on a metal substrate that allows efficient metal back contact for device integration [15]. Recently, nanostructures of various metal oxides have been successfully synthesized by using anodizing, including Al 2 O 3 [16][17][18][19], ZnO [20,21], CuO [22], Cu 2 O [15] and TiO 2 [23]. For the fabrication of nanostructures by anodizing of copper, only few studies have been reported, involved in the fabrication of CuO [22], Cu(OH) 2 [22] and Cu 2 O [15] nanostructures.…”
Section: Introductionmentioning
confidence: 99%